2015
DOI: 10.3892/br.2015.476
|View full text |Cite
|
Sign up to set email alerts
|

Glucose plus metformin compared with glucose alone on β-cell function in mouse pancreatic islets

Abstract: Metformin is currently the first drug of choice for treatment of type II diabetes. The primary function of metformin is to decrease hepatic glucose production mainly by inhibiting gluconeogenesis. The aim of the present study was to investigate the effects of glucose alone (control groups) and glucose and metformin (treatment groups) on pancreatic islets functions. Pancreatic islets were isolated by collagenase digestion and incubated for 24 or 48 h in RPMI-1640 containing 5 mmol/l glucose (control groups 1 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…Using murine islets and human islets Lundquist et al [37] have demonstrated a marked reduction by metformin [20 μM] in nitric oxide synthase-derived nitric oxide, insulin secretory dysfunction and loss in cell viability under conditions of long-term exposure to glibenclamide and HG. Using rodent islets, Hashemitabar and associates have demonstrated beneficial effects of metformin [15 μM] on insulin gene expression, insulin secretion and islet cell viability [38]. Natalichhio and coworkers have shown significant restoration of GLP-1 receptor impairment by metformin [0.5–1.0 mM] in murine islets following exposure to palmitate [39].…”
Section: Discussionmentioning
confidence: 99%
“…Using murine islets and human islets Lundquist et al [37] have demonstrated a marked reduction by metformin [20 μM] in nitric oxide synthase-derived nitric oxide, insulin secretory dysfunction and loss in cell viability under conditions of long-term exposure to glibenclamide and HG. Using rodent islets, Hashemitabar and associates have demonstrated beneficial effects of metformin [15 μM] on insulin gene expression, insulin secretion and islet cell viability [38]. Natalichhio and coworkers have shown significant restoration of GLP-1 receptor impairment by metformin [0.5–1.0 mM] in murine islets following exposure to palmitate [39].…”
Section: Discussionmentioning
confidence: 99%
“… 343 Furthermore, it supports weight loss 344 by reducing food consumption. 345 With respect to its effects on β-cell function, metformin was shown to increase insulin gene expression, 346 possibly by nuclear accumulation of pdx1 and its subsequently improved DNA-binding activity. 347 Interestingly, metformin exerts opposing effects on β-cell proliferation and/or apoptosis; on the one hand, it suppresses β-cell proliferation and enhances apoptosis through an AMPK-dependent and autophagy-mediated mechanism 348 following the metformin-induced activation of c-Jun-N-terminal kinase and caspase-3.…”
Section: Modulating Insulin Secretion As a Means Of Diabetes Therapymentioning
confidence: 99%
“…Metformin is a widely used drug of T2DM, and its antidiabetic characteristics should be inhibiting hepatic gluconeogenesis and improving insulin sensitivity in peripheral tissues (Adak, Samadi, Unal, & Sabuncuoglu, ). Based on previous in vivo studies, metformin also can increase glucose oxidation in MIN6 pancreatic β cells, promote insulin release in mouse isolated pancreatic islets (Hashemitabar, Bahramzadeh, Saremy, & Nejaddehbashi, ), and alleviate functional, biochemical, and ultrastructural abnormalities in human islet cells exposed to glucotoxic condition. But so far, the effect and underlying mechanisms of metformin on β cells remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…. Based on previous in vivo studies, metformin also can increase glucose oxidation in MIN6 pancreatic β cells, promote insulin release in mouse isolated pancreatic islets (Hashemitabar, Bahramzadeh, Saremy, & Nejaddehbashi, 2015), and alleviate functional, biochemical, and ultrastructural abnormalities in human islet cells exposed to glucotoxic condition. But so far, the effect and underlying mechanisms of metformin on β cells remain unclear.…”
mentioning
confidence: 99%